PERLINDUNGAN HUKUM BANK SYARIAH SEBAGAI KREDITUR ATAS COVERNOTE NOTARIS PADA PEMBIAYAAN MURABAHAH - Tiara Aisyah; Hasbir Paserangi; Muhammad Ilham Arisaputra (El-Iqthisadi, 2022)
Abstract This study aims to analyze the Legal Protection of Islamic Banks as Creditors for Notary Covernotes with Problems in Murabahah Financing, where banks as creditors in using notary covernotes as one of the considerations in disbursing murabaha funds must pay attention to the application of the precautionary principle and when the notary's covernote and what kind of efforts can be made by banks as creditors for Covernote which have problems in murabahah financing. This research uses the type of empirical legal research, this research uses field data as the main data source, such as the results of interviews. The results of the study show that the application of the prudent principle plays an important role in the banking system because it is used as indirect protection by the bank for the interests of depositors and their deposits at the bank. This principle is used to prevent the risk of loss arising from a policy and business activities carried out by a bank. Bank's efforts as a creditor for a notary's covernote that has problems in murabahah financing, when a notary's covernote has problems that make credit or customer financing also problematic, the bank uses efforts, namely through litigation and non-litigation processes, to a notary whose covernote is problematic and results in losses for the bank, the efforts made by the bank namely the bank will ask the notary to complete what is stated in the covernote or improve the covernote, if this does not get results then the bank will report the notary to the Regional Supervisory Council. Keywords: Covernote, Default, Murabahah Financing.